1999
DOI: 10.1046/j.1365-2125.1999.00090.x
|View full text |Cite
|
Sign up to set email alerts
|

A mechanism‐based pharmacokinetic‐enzyme model for cyclophosphamide autoinduction in breast cancer patients

Abstract: The presented mechanism-based enzyme induction model where the pharmacokinetics of the inducer and the enzyme pool counterbalance each other successfully described CP autoinduction. It is reasonable to believe that CP affects its own elimination by increasing the enzyme production rate and thereby increasing the amount of enzyme by which CP is eliminated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
49
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 39 publications
(75 reference statements)
5
49
1
Order By: Relevance
“…It is known that the disposition of highdose CY by the CYP450 enzymes is a saturable process 50 while on the other hand, CY also shows autoinduction. 21,24,25,49 Hence, the increase in AUC and decrease in Cl of CY that we observed on day 4 in some of our patients in this study could be due to nonpredictable variations in the balance between enzyme saturation and autoinduction.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…It is known that the disposition of highdose CY by the CYP450 enzymes is a saturable process 50 while on the other hand, CY also shows autoinduction. 21,24,25,49 Hence, the increase in AUC and decrease in Cl of CY that we observed on day 4 in some of our patients in this study could be due to nonpredictable variations in the balance between enzyme saturation and autoinduction.…”
Section: Discussionmentioning
confidence: 85%
“…21,24,25,49 Several studies have shown detectable autoinduction of CY within 24 h after the initiation of CY infusion resulting in shorter CY T1/2, increased Cl/F and decreased AUC. 21,24,25,49 The AUC of CY was increased and Cl decreased (Figure 3) after the fourth dose in as many as half of the patients included in this study. Phenytoin was used to prevent BU-induced seizures, and hence residual effects of phenytoin upon drug metabolism and transport would be present for day 1 but not for day 4.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,9,20 Part of the variation was considered to be caused by regulatory phenomena at the transcriptional or translational level. 5,21,22 Subsequently, genetic polymorphism of this enzyme was discovered 23,24 and this contributes to the variation. An amino-acid substitution, Gln 172 His, caused by the G516T (CYP2B6*6) SNP was described to enhance 7-ethoxycoumarin O-deethylase activity.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23] Through this course, CYP2C9, CYP2B6, and CYP3A4 are induced in human hepatocytes; this mechanism is called autoinduction. 24,25 Autoinduction results in the increased clearance of the drug during treatment with an increased formation of 4-HC, phosphoramide mustard, and 2-dechloroethylcyclophosphamide. 22,23,[26][27][28][29][30] In general, autoinduction is detectable within 24 h of administration.…”
Section: Centration; Conditioning Regimen; Drug Interactionmentioning
confidence: 99%